Social citizenship and ethnicity around a public sector steel plant in Orissa, India - Strümpell, Christian (Citizenship studies, 2011)
This article is about a modern public sector steel plant in the state of Orissa and its promise to set standards for post-colonial India's citizenry at large. These steel plants were to provide their workforces with superior social and economic citizenship rights, which in turn were to serve as exemplary industrial relations for the industrialising nation. The steel plants were also intended to forge multi-ethnic workforces into exemplary Indian citizens by transcending their manifold ethnic differences. The trajectory of the public sector steel plant in the town of Rourkela confirms that enhanced social and economic citizenship rights detached public sector steel workforces from labour at large and produced a ‘labour aristocracy’. The trajectory, furthermore, reveals how in Rourkela policies designed to accommodate ethnic differences constantly recreated these differences and hampered the access of large sections of the local population to these enhanced social and economic citizenship rights.